Physiological functions of APP family proteins - Müller, Ulrike C.; Zheng, Hui (Cold Spring Harbor perspectives in medicine, 2012)
Biochemical and genetic evidence establishes a central role of the amyloid precursor protein (APP) in Alzheimer disease (AD) pathogenesis. Biochemically, deposition of the β-amyloid (Aβ) peptides produced from proteolytic processing of APP forms the defining pathological hallmark of AD; genetically, both point mutations and duplications of wild-type APP are linked to a subset of early onset of familial AD (FAD) and cerebral amyloid angiopathy. As such, the biological functions of APP and its processing products have been the subject of intense investigation, and the past 20+ years of research have met with both excitement and challenges. This article will review the current understanding of the physiological functions of APP in the context of APP family members.